Role of Waddlia chondrophila Placental Infection in Miscarriage - Baud, David; Goy, Geneviève; Osterheld, Maria-Chiara; Croxatto, Antony; Borel, Nicole; Vial, Yvan; Pospischil, Andreas; Greub, Gilbert (Emerging infectious diseases, 2014)
Waddlia chondrophila is an intracellular bacterium suspected to cause human and bovine abortion. We confirmed an association between antibodies against W. chondrophila and human miscarriage and identified this organism in placenta or genital tract of women who had had miscarriages. These results suggest a possible role of W. chondrophila infection in miscarriage.